Heat dissipating upper body compression garment: Thermoregulatory, cardiovascular, and perceptual responses - Iker Leoz-Abaurrea; Nicholas Tam; Roberto Aguado-Jiménez (Elsevier, 2019)
Purpose: The aim of the present study was to determine the effects of an upper body compression garment (UBCG) on thermoregulatory responses during cycling in a controlled laboratory thermoneutral environment (~23°C). A secondary aim was to determine the cardiovascular and perceptual responses when wearing the garment. Methods: Sixteen untrained participants (age: 21.3 ± 5.7 years; peak oxygen consumption (VO2peak): 50.88 ± 8.00 mL/min/kg; mean ± SD) performed 2 cycling trials in a thermoneutral environment (~23°C) wearing either UBCG or control (Con) garment. Testing consisted of a 5-min rest on a cycle ergometer, followed by 4 bouts of cycling for 14-min at ~50%VO2peak, with 1-min rest between each bout. At the end of these bouts there was 10-min of passive recovery. During the entire protocol rectal temperature (Trec), skin temperature (Tskin), mean body temperature (Tbody), and heat storage (HS) were measured. Heart rate (HR), VO2, pH, hematocrit (Hct), plasma electrolytes, weight loss (Wloss), and perceptual responses were also measured. Results: There were no significant differences between garments for Tskin, HS, HR, VO2, pH, Hct, plasma electrolyte concentration, Wloss, and perceptual responses during the trial. Trec did not differ between garment conditions during rest, exercise, or recovery although a greater reduction in Trec wearing UBCG (p = 0.01) was observed during recovery. Lower Tbody during recovery was found when wearing UBCG (36.82°C ± 0.30°C vs. 36.99°C ± 0.24°C). Conclusion: Wearing a UBCG did not benefit thermoregulatory, cardiovascular, and perceptual responses during exercise although it was found to lower Tbody during recovery, which suggests that it could be used as a recovery tool after exercise. Keywords: Body temperature, Compression garment, Cycling, Heat dissipation, Thermoregulation